Techniki perswazyjne w radiowych tekstach dziennikarskich na przykładzie serwisów informacyjnych „Fakty RMF FM” (czerwiec–sierpień 2013) - Piotrkowski, Maciej Sergiusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The author analyses the role of the radio news bulletin, based on the example of “Fakty” on the RMF FM radio station. In this, he uses the theory of persuasive techniques researched by M. Gajlewicz; however, he also takes into account linguistic aspects of the communication and modern rhetoric understood as effective persuading. The purpose of the article is to prove that radio news on a commercial radio station is not actually just “pure” information; a neutral informative style is consequently displaced by the rhetorical style, full of intentionally used linguistic mechanisms, to make the information more persuasive.